Evaluation of the use of flood attenuation controls for the management of urban stormwater impacts in Cape Town, South Africa - Hotchkiss, Timothy Stephen (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.